2010
DOI: 10.1136/bjsm.2010.078972.13
|View full text |Cite
|
Sign up to set email alerts
|

Postural assessment and joint instability in athletes of federated Brazilian swimmers

Abstract: Swimming training imposes a considerable stress about the joint and musculoskeletal structures. This study aimed to identify the postural changes and joint instabilities of federated Brazilian swimming. The authors evaluated 60 swimmers, 29 (48%) women and 31 (52%) men, with an average age of 20±3 years. To appraise the joint instabilities, the authors performed the drawer tests on anterior and posterior shoulder, sulcus test, drawer test anterior and posterior knee, stress test abduction (valgus) and stress t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Spinal health is a common concern in all kinds of sports. Several studies have reported the prevalence of scoliosis among the athletes engaged in ballet and dance,1 3–5 gymnastics,6 volleyball7 and swimming 8 9. The prevalence of IS is higher in women with a curvature equal to or greater than 10° 10…”
Section: Introductionmentioning
confidence: 99%
“…Spinal health is a common concern in all kinds of sports. Several studies have reported the prevalence of scoliosis among the athletes engaged in ballet and dance,1 3–5 gymnastics,6 volleyball7 and swimming 8 9. The prevalence of IS is higher in women with a curvature equal to or greater than 10° 10…”
Section: Introductionmentioning
confidence: 99%